Evolution of mass, surface layer composition and light scattering of evaporating, single microdropletes of SDS/DEG suspension. Shrinking droplet surface as the micelles generator. (January 2021) - Kolwas, Maciej; Jakubczyk, Daniel; Archer, Justice; Duc, Tho Do
Highlights: Single evaporating microdroplets of SDS/DEG suspension are levitated in EDB. Light scattering technique is used for microdroplet characterisation. Evolution of droplet mass, surface layer composition and light scattering is studied. Cyclic creation of micelles at the droplet surface is proposed and discussed. Critical micelles concentration of SDS in DEG is determined. Abstract: We study the evolution of the mass of evaporating single microdroplets of sodium dodecyl sulphate (SDS) / diethylene glycol (DEG) mixture. First, we recognise and deconvolute the influence of residual water evaporation [Kolwas et al. Soft Matter 2019;15:1825], which accelerates the composite droplet evaporation, a simple exponential decay of the evaporating droplet surface change rate. This enables us to study the influence of SDS concentration on the composite droplet evaporation. Next, we establish a simple relationship between the average SDS concentration and the droplet evaporation rate to enable the study of the evolution of SDS concentration at the droplet surface. The oscillatory nature of surface SDS concentration indicates cyclic changes in the surface monolayer associated with the cyclic creation of vesicles (micelles) at the surface. The model we developed, allows determination of SDS critical micelles concentration (CMC) in DEG as 60±2 mM. Graphical abstract: Image, graphical abstract